Novel surgical methods in Descemet's membrane endothelial keratoplasty. (December 2013) - Yoeruek, Efdal; Bartz-Schmidt, Karl-Ulrich
Endothelial keratoplasty is continually evolving both in surgical technique and clinical outcomes. The latest development of posterior lamellar surgery represents Descemet's membrane endothelial keratoplasty (DMEK) introduced by Melles from Rotterdam. This leaves a secure eye with less postoperative astigmatism, a faster visual rehabilitation and better optical quality when compared with other posterior keratoplasty techniques. Despite the recent advances in posterior lamellar surgery techniques, the preparation of the Descemet's membrane (DM) and the unfolding in the anterior chamber in DMEK still poses a risk of complication during surgery. Today, despite the fact that the availability of donor tissues prepared by a steadily increasing number of eye banks worldwide should have boosted the feasibility of DMEK in many endothelial disorders, yet membrane dissection and intraoperative graft unfolding difficulties hinder the implementation of the aforesaid technique. Therefore, further efforts are needed for improving current surgical techniques of donor preparation, insertion and unfolding. In this review, surgical methods of DM's preparation and unfolding techniques in the anterior chamber are summarized.